Modelling bentonite–water interactions at high solid/liquid ratios: swelling and diffuse double layer effects - Wersin, P; Curti, E; Appelo, C.A.J (Applied clay science, 2004)
Previous experimental studies on bentonite–water interactions have demonstrated the importance of ion exchange and surface complexation reactions occurring at the clay surface as well as dissolution/precipitation reactions of mineral impurities. Based on these findings, thermodynamic models have been widely used to derive porewater compositions for the compacted bentonite used as backfill material for nuclear repositories. Conventional models typically neglect phenomena important in compacted clays such as anion exclusion induced by swelling of the expandable clay fraction and by the formation of electrical double layers on charged edge surfaces. In this study, we evaluate such phenomena by applying a refined diffuse double layer (DDL) approach to model porewater composition in a compacted bentonite backfill surrounded by argillaceous host rock, as foreseen for the Swiss high-level waste repository. Model calculations also include the effect of water incorporation in the structural interlayers. The results indicate that the conventional model and the refined DDL model without distinction between interlayer and external water only differ slightly. The main buffering reactions include ion exchange of Ca for Na, calcite and gypsum dissolution and deprotonation of surface hydroxyl groups. On the other hand, the calculation accounting for the distinction of external and interlayer water indicates significant anion exclusion effects on the external water composition. Most notably, this leads to an increased salinity and drop in pH. From a performance assessment perspective, however, the differences induced by the inclusion of swelling and diffuse double layer effects are not very significant relative to uncertainties related to system variables, such as the pCO 2 of the host rock. Finally, it should be emphasised that significant uncertainties related to the thermodynamic properties of water in compacted clays, e.g., dielectric constant, are still unresolved and deserve further investigations.